A place where three roads meet: theory, humanities and research (2015)
This article argues that theory has become a dominant sign of our time and has moved beyond its traditional engagement with literary text but addresses a wider range of socio-political and cultural concerns worldwide; embracing most disciplines of the humanities and the social sciences. Literary theory for instance, now includes the subject, minorities, identities, race, class, gender -empire,' colony, nation, migrancy, centre, margin, postcoloniality, civil war, global refugee crises, globalization among others. Theory, as a result, is not a mere instrument that we use anyhow but. rather it should be carefully chosen before we apply it to our research. Today, theory is very important that hardly can we engage in a humanistic study without applying theories. To be a critic now, especially in academic life, is also to be a theorist. The essay concludes by noting that Humanities and Research cannot operate in isolation for they walk and work together and that any serious researcher has to be mindful of this.